IMPLEMENTASI PERMAINAN TRADISIONAL TEJOG TALI DALAM MELATIH PERKEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN - Poniati, Ni Made Novi; Anadhi, I Made Gede; Dewi indriati, Nyoman Utari Nyoman Utari (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
The traditional game of tejog tali is an activity involving two groups, where one group acts as a player and the other group acts as a substitute. In this game, players walk on bamboo while holding on to a rope to maintain balance. This research uses qualitative or descriptive methods to examine the implementation of the tejog tali game in training the gross motor development of children aged 5-6 years at Mas Kumara Kindergarten. Data collection was carried out through interviews and observations. The data analysis technique used is descriptive analysis. The results of the research show that playing tejog rope can effectively improve children's gross motor skills. Children who engage in this game not only develop their gross motor skills, but also the ability to focus and concentrate on achieving goals. It can be concluded that the implementation of the traditional game tejog tali can improve the gross motor development of children aged 5-6 years.